DNA methylation profiles after ART during human lifespan: a systematic review and meta-analysis. (8th March 2022) - Barberet, Julie; Ducreux, Bastien; Guilleman, Magali; Simon, Emmanuel; Bruno, Céline; Fauque, Patricia
Abstract: BACKGROUND: The many manipulations and processes used in ART coincide with the timing of epigenetic reprogramming and imprinting during female gametogenesis and pre-implantation embryo development, leading to concerns that the actual ART could negatively affect epigenetic reprogramming and imprinting in gametes and early embryos. A growing body of literature suggests that ART may affect epigenetic marks, such as DNA methylation, in the fetus and placenta. Potentially, this may be responsible later in life for the increased risk of adverse outcomes associated with ART. Unfortunately, the conclusions are inconsistent and, despite the increasing usage of ART, its safety at the epigenetic level is still not established. OBJECTIVE AND RATIONALE: To examine whether ART is associated with DNA methylation modifications and if these modifications persist throughout life, we provide an update on the current understanding of epigenetic reprogramming in human gametes and embryos, and then focus on the assessment of fetal and postnatal DNA methylation modifications that may remain until adulthood following the use of ART in humans. SEARCH METHODS: We reviewed studies using targeted or epigenome-wide techniques to assess the DNA methylation patterns of the conceptus after ART compared with natural conceptions. A search for relevant studies was performed in the PubMed and EMBASE databases on 15 July 2021 with an extensive search equation. Studies on animals, gametes and embryos were subsequently excluded. After an in-depth review of full-text articles, studies on specific populations with imprinting disorders were removed and not further discussed. Before comprehensive analysis, the risk of bias of each included study was assessed with the Newcastle–Ottawa scale and quality of evidence was graded using the Grading of Recommendations, Assessment, Development and Evaluations criteria. OUTCOMES: In total, 928 records were initially identified, and 51 were finally included in the systematic review. Given the variability in the genomic scale at which DNA methylation was measured in the different studies, they were separated into two categories: targeted DNA methylation or genome-wide DNA methylation study. The present systematic review has made it possible to assess a substantial number of children since more than 4000 DNA methylation profiles of ART concepti were compared to more than 7000 controls. There is evidence that ART conception is associated with aberrant DNA methylation in imprinted loci and other genes in various tissues. One isolated modification notably occur in the paternally expressed gene 1/mesoderm-specific transcript homologue ( PEG1/MEST) region, and we cannot rule out other studied sequences owing to the heterogeneity of the evidence base. WIDER IMPLICATIONS: Differences in DNA methylation after ART conceptions are modest, and the functional relevance in adult tissues is unknown. Functional effects in terms of gene expression as well as the roles of other epigenetic marks need to be further explored. Moreover, there is little overlap of findings obtained in targeted and genome-scale analyses owing to the lack of comparability of CpGs analyzed between both techniques. This issue also stems from small sample sizes and marked differences in methodology and cohort characteristics. Standardization of methodologies and large collaborative efforts are required to reduce the inconsistency of results and increase the robustness of findings. Finally, further studies are required to determine the contribution of parental infertility per se from the ART treatment.